The complete mitochondrial genome of the oleaginous microalgae Ankistrodesmus falcatus strain UCP001 from the Peruvian Amazon - Cobos M. (2021)
Ankistrodesmus falcatus strain UCP001 is a native oleaginous microalgae isolated from the Peruvian Amazon basin. In this study we sequenced, de novo assembled, and functionally annotated the complete mitochondrial genome of the native oleaginous microalgae Ankistrodesmus falcatus strain UCP001 (Accesion number MT701044). This mitogenome is a typical circular double stranded DNA molecule of 41,048 bp in total length with G + C content of 37.4%. The mitogenome contains 49 genes, including 18 protein coding genes, 5 ribosomal (rRNA) genes and 26 transfer RNA (tRNA) genes. A phylogenetic analysis of 18 microalgae species indicated that Ankistrodesmus falcatus strain UCP001 was closely related to Ourococcus multisporus and Raphidocelis subcapitata. The complete mitochondrial genome sequence of Ankistrodesmus falcatus strain UCP001 enriches genomic resources of oleaginous native microalgae from the Peruvian Amazon for further basic and applied research. © 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.